Retroperitoneal laparoscopic partial resection of the renal pelvis for urothelial carcinoma: A case report - Wang, Yan-Long (World J Clin Cases, 2021)
BACKGROUND: The standard treatment of transitional cell carcinoma of the upper urinary tract consists of radical nephroureterectomy with bladder cuff removal, which can be performed either in open or laparoscopy or robot-assisted laparoscopy. Treatment of chronic renal insufficiency patients with upper urothelial tumor is in a dilemma. Urologists weigh and consider the balance between tumor control and effective renal function preservation. European Association of Urology guidelines recommend that select patients may benefit from endoscopic treatment, but laparoscopic treatment is rarely reported. CASE SUMMARY: In this case report, we describe a case of 79-year-old female diagnosed with urothelial carcinoma of the renal pelvis and adrenal adenoma with chronic renal insufficiency. The patient was treated with retroperitoneal laparoscopic partial resection of the renal pelvis and adrenal adenoma resection simultaneously. CONCLUSION: Retroperitoneal laparoscopic partial resection of the renal pelvis is an effective surgical procedure for the treatment of urothelial carcinoma of the renal pelvis.